2006
DOI: 10.1523/jneurosci.1158-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Functional Connectivity between Dorsal Premotor and Contralateral Motor Cortex during Movement Selection

Abstract: The left dorsal premotor cortex (PMd) is thought to play a dominant role in the selection of movements made by either hand. We used transcranial magnetic stimulation to study the functional connectivity of the left PMd and right primary motor cortex (M1) during an acoustic choice reaction time (RT) task involving contraction of the thumb and forefinger. The facilitatory and inhibitory pathways that can be demonstrated between left PMd and right M1 at rest were suppressed during most of the reaction period. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
223
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(267 citation statements)
references
References 27 publications
41
223
3
Order By: Relevance
“…In both of these control experiments the IPI was 6 ms, as in the switch and stay experiments. These control experiments are thus not comparable with previous paired-pulse TMS experiments probing PMd/M1 functional connectivity, which used an IPI of 8 ms (Koch et al, 2006;O'Shea et al, 2007).…”
Section: Methodscontrasting
confidence: 57%
See 1 more Smart Citation
“…In both of these control experiments the IPI was 6 ms, as in the switch and stay experiments. These control experiments are thus not comparable with previous paired-pulse TMS experiments probing PMd/M1 functional connectivity, which used an IPI of 8 ms (Koch et al, 2006;O'Shea et al, 2007).…”
Section: Methodscontrasting
confidence: 57%
“…We then probed the differential influence of pre-SMA on M1 depending on the cognitive state of the participants, i.e., whether participants executed the prepared response or switched to another response. Previous studies of functional connectivity between dorsal premotor cortex (PMd) and M1 have reported changes time-locked to task events (Koch et al, 2006;O'Shea et al, 2007), suggesting the technique may be suitable for probing the influence of pre-SMA on M1 during cognitive control of action selection.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we decided post hoc to perform, alongside to the main analysis, a conventional analysis based on averaging all MEPs within conditions and computing the ratio between the grand averages of the dualpulse trials and that of the single-pulse trials as is generally done in dual-coil TMS experiments (Davare et al 2009;Koch et al 2006;Mars et al 2009;O'Shea et al 2007b). For each subject, we thus obtained 15 values (three TAR-GETS × five ISIs) values of the single-pulse/dual-pulse MEPs ratio.…”
Section: Control Analysesmentioning
confidence: 99%
“…We provide evidence for a specific short-latency inhibitory effect of the The connectivity between the PMC and the ipsilateral M1 in humans is largely hypothesized by analogy with the non-human primates. Still, direct evidence for it has been obtained by means of the dual-coil paradigm of transcranial magnetic stimulation (TMS) (Baumer et al 2009;Cattaneo and Barchiesi 2011;Civardi et al 2001;Davare et al 2008Davare et al , 2009Davare et al , 2010Koch et al 2006;Mars et al 2009). This protocol involves the use of two magnetic stimulators connected to two distinct coils, both of which are used simultaneously on the participant's scalp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation